Strengthening Religious Moderation Through Nalar Strategies as a Deradicalization Effort in the Indonesian Migrant Worker Community - Heriyudanta, Muhammad; Arisona, Risma Dwi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
One of Indonesia's problems is the issue of radicalism. Those who are vulnerable to radicalism are Indonesian migrant workers. Because many Indonesian migrant workers are entangled in radical ideas, preventive and curative efforts are significant. This community service aims to strengthen religious moderation through the NALAR strategy as an effort to deradicalize the Indonesian migrant worker community (KOPI) in Ponorogo. This method of community service is Community Based Research (CBR). The technique used in the process of community-based Research (CBR) activities is the Participatory Action Research (PAR) approach. Based on the results of the discussion, it was concluded that there are four indicators of moderation in religion: nationality, tolerance, Anti-racialism, and culture, which are then abbreviated as NALAR. We then made NALAR a strategy to provide assistance and strengthen religious moderation for the Indonesian migrant worker community. Second, NALAR was internalized by the community service team as an effort to deradicalize the Indonesian migrant worker community in Ponorogo. The service team explained the concept of religious moderation, indicators of religious moderation, and the urgency of religious moderation for Indonesian migrant workers in Ponorogo. Third, the evaluation results in terms of the level of knowledge of religious moderation of KOPI members are very good.